Co-inoculation of Lactiplantibacillus pentosus 1 and Saccharomyces cerevisiae 31 for a salt-free fish sauce production from channel catfish (Ietalurus punetaus) bone. (December 2022) - Gao, Pei; Zhang, Zhiqing; Ge, Yi; Cao, Shining; Zhang, Xiaojing; Jiang, Qixing; Xu, Yanshun; Xia, Wenshui; Liu, Shaoquan
Abstract: The study aimed to evaluate the co-inoculation of non-fish sauce strains for a fish sauce production made from Ietalurus punetaus fish bone hydrolysate (FBH) without salt addition. Individual inoculation ( Lactiplantibacillus pentosus 1, LP and Saccharomyces cerevisiae 31, SC), and co-inoculation of both strains (FS) were employed, including an uninoculated control. Both strains exhibited good growth in FBH without salt addition. Compared with individual inoculation and uninoculated control, co-inoculation (FS) produced acid and amino nitrogen more quickly, as well as displaying higher sugar consumption. No significant difference was observed in trichloroacetic acid (TCA)-soluble peptides among all groups ( P > 0.05). Moreover, significantly lower levels of six bitter amino acids were observed after co-fermentation ( P < 0.05). In addition, more alcohols, esters and acids with pleasant notes and fewer unsaturated aldehydes with fishy note were generated after co-inoculation, in the absence of traditional fish sauce off-odor notes. The study demonstrated that the co-inoculation of non-fish sauce strains were appropriate for producing a salt-free fish sauce with better flavor. Highlights: Channel catfish bone hydrolysate without salt was used for fish sauce production. L. pentosus 1 and S. cerevisiae 31 were employed as the mixed inoculum. The two strains exhibited good fermentation performance in the bone hydrolysate. More pleasant flavor notes and fewer off-odor notes were observed with inoculation. The co-inoculation was fit for producing a saltless fish sauce with better flavor.